2020
DOI: 10.1038/s41598-020-59628-6
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Pilot Study on Sex and Spinal Cord Injury Shows Sexual Dimorphism in Functional Recovery and Cardio-Metabolic Responses

Abstract: More than a quarter of a million individuals in the US live with spinal cord injury (Sci). Sci disrupts neural circuitry to vital organs in the body. Despite severe incidences of long-term peripheral complications from Sci, the cardio-metabolic consequences and divergences in sex-related responses are not well described. We examined the effects of SCI on functional recovery, cardiac structure and function, body composition, and glucose metabolism on adult female and male Sprague Dawley (SD) rats. Sci was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…This could possibly have been because of the small sample size and the inclusion of both males and females, in that sexual dimorphisms following SCI have been identified in rodents, although they remain controversial. [55][56][57][58] Another factor that may have contributed to the variability in circulating neutrophil activity on day 0 could have been the variability in injury severity among SCI dogs. Another possibility for the lack of significant difference in day 0 neutrophil activity between SCI and healthy dogs was the inclusion of dogs whose initial clinical signs had first been noticed up to 48 hours earlier.…”
Section: Discussionmentioning
confidence: 99%
“…This could possibly have been because of the small sample size and the inclusion of both males and females, in that sexual dimorphisms following SCI have been identified in rodents, although they remain controversial. [55][56][57][58] Another factor that may have contributed to the variability in circulating neutrophil activity on day 0 could have been the variability in injury severity among SCI dogs. Another possibility for the lack of significant difference in day 0 neutrophil activity between SCI and healthy dogs was the inclusion of dogs whose initial clinical signs had first been noticed up to 48 hours earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The different outcomes seen in these previous reports could be due to their differences in model animals, injury models, SCI location and severity, and sample sizes. In a previous pilot study reported by our group, we compared cardiometabolic and BBB outcomes in adult male and female rats and observed differences in the BBB and various cardiometabolic effects according to sex after severe contusion SCI ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously conducted a study on severe contusion at T10 in female and male rats (a 10-g rod dropped from a height of 35 mm), finding improved motor outcomes by BBB for female rats and altered metabolic parameters by sex ( 32 ). For this follow-up study, we compared outcomes for severe contusion SCI and included additional sensorimotor outcome measures and more extensive histological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were scanned with echocardiogram to assess cardiac structure and function at different time points as previously described [59]. Mice were imaged under anesthesia with isoflurane (induction at 3% and then maintained on 1.5%) with a heart rate of 400 to 500 beats per minutes.…”
Section: Echocardiography Analysismentioning
confidence: 99%
“…To ensure comparison between all measurements, focus was emphasized on the midventricular level of the heart, by identifying the papillary muscles. Left ventricle measurements were performed using the auto LV analysis tool by tracing the internal diameters of the ventricle, averaged from three consecutive cycles for each animal [59][60][61][62][63]. To limit noise caused by respiratory movements, images were acquired when the mice was not actively breathing, as assessed with the respiratory rate provided with the ultrasound system.…”
Section: Echocardiography Analysismentioning
confidence: 99%